POLY(VINYL ALCOHOL) AND POLY(VINYL ALCOHOL) /ZINC OXIDE COMPOSITE NANOFIBRE WEBS: QUALITY CONTROL WITH CONDUCTOMETER (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
In the market a wide variety of products are find that contains/releases metal nanoparticles, therefore topical become researches on it impacts on the environment and human health. In the textile industry important step is the development of testing methodology to monitor the quantity of nanoparticles that get into the environment from nanoparticles containing textile materials. In the study analyzed the method based on the use of conductometer for textiles testing with nano-size metal oxides content to determine the persistence of nanoparticles/ions in the water after textile soaking/washing. Compared results acquired in the experiments with nanofibre webs manufactured by electrospinning from pure polyvinyl alcohol (PVA) and PVA/ZnO composite. The nanofibre webs were soaked in distilled water and obtained samples of water tested with conductometer. The results of the experiments confirm that measurements taken with the conductometer are fairly stable and repeatable; the equipment is suitable for measurements in distilled water for nanoparticles/ions detection. The measurements of the solution’s specific electric conductance allows to pinpoint the nanoparticles/ions concentration, but for this purpose, must be created the database that contains the resources needed for the calculations and methodology for sample preparation.